2007
DOI: 10.1017/s026646740700421x
|View full text |Cite
|
Sign up to set email alerts
|

Visual assessment of wilting as a measure of leaf water potential and seedling drought survival

Abstract: Rainfall and soil moisture availability vary greatly both spatially and temporally. They are prime factors influencing species distribution patterns, diversity and habitat associations in a range of biomes, and limit primary productivity in many natural ecosystems, as well as in forestry and agricultural systems (Hawkins et al. 2003, Kozlowski & Pallardy 1997, Lieth 1975). Projections of drying trends, and increased frequency and intensity of drought events with climate and land-use changes (Hulme & Vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 25 publications
1
49
1
Order By: Relevance
“…The initial large drought screen of 138 different Brachypodium ecotypes highlighted the considerable variation in the size and stature between the ecotypes, both in well-watered and drought stressed conditions. Wilting scores are the most widely used indicator for plant drought stress and have been shown to allow for robust ranking of survival when exposed to drought (Engelbrecht et al, 2007). Hence, visual assessment of plant wilting ( Supplementary Table S2 ) formed the basis for the selection of those ecotypes to be included for a second, more refined drought screen.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial large drought screen of 138 different Brachypodium ecotypes highlighted the considerable variation in the size and stature between the ecotypes, both in well-watered and drought stressed conditions. Wilting scores are the most widely used indicator for plant drought stress and have been shown to allow for robust ranking of survival when exposed to drought (Engelbrecht et al, 2007). Hence, visual assessment of plant wilting ( Supplementary Table S2 ) formed the basis for the selection of those ecotypes to be included for a second, more refined drought screen.…”
Section: Resultsmentioning
confidence: 99%
“…Total water withdrawal began 28 days after sowing and lasted 6 days. Leaf wilting was scored by two individuals according to a 1–6 scale for this trait (1 = no effect, 6 = severe effect) based on the visual assessment categories described by Engelbrecht et al (2007). Plants were weighed immediately after harvest of the above ground biomass.…”
Section: Methodsmentioning
confidence: 99%
“…This measure of desiccation tolerance corresponds closely with seedling performance under drought conditions in the field (Tyree et al . 2003; Engelbrecht et al . 2007b) and represents the lowest water potential and RWC values associated with living leaf tissue (Ludlow 1989; Auge et al .…”
Section: Methodsmentioning
confidence: 99%
“…Leaf wilting was scored on a scale of 1-4 modified from Engelbrecht et al [13] as 1 = no wilting; 2 = slightly wilting; 3 = wilting, wherein the plant showed leaf wilting only during hot hours from which the leaves recovered; 4 = severe wilting, wherein wilted leaves did not recover. The stress treatment did not go as far as killing plants, and therefore, death level was eliminated.…”
Section: Visual Scoringmentioning
confidence: 99%